Tuesday

March 31, 2015

March 31, 2015

Posted by **Dj** on Thursday, May 15, 2008 at 6:35pm.

3x + 4y = 0

y = x you have to substituted the y for x

Then the same other problem with different number.

y = x

-6x + 8y = -2

- math -
**Reiny**, Thursday, May 15, 2008 at 7:33pmsince y = x

in the first equation

3x + 4y = 0

3x + 4(x) = 0

7x = 0

x = 0 , since y=x, y = 0

do the same thing in the second problem.

- math -
**Dj**, Thursday, May 15, 2008 at 7:57pmThank you Reiny you really help me.

- math -

**Answer this Question**

**Related Questions**

MATH/ALGEBRA PLEASE - I am having a real issue with this one problem the problem...

algebra 1 - Can someone please help me with this inequality problem -3-8>(4x+...

Math - 3x-4 to y+15 is constant and y=3 when x=2 then when y=12, x equals? My ...

Math - How would you solve this problem?: x2 + y2 = 25 x2 - y = 5 You have to ...

pre calculus - Hi, I am having a problem trying to find and understanding how ...

pre calculus - Hi, I am having a problem trying to find and understanding how ...

English - 1. The hospital is for certain people. 2. He has a certain problem. 3...

Algebra - Please read and then help me! (x^(-3/5)) ----------- divide x ^ (1/5) ...

Math 3 - graphing log functions for y=log12^x I don't have a calculator for this...

Calculus - Given two problems: Problem A: Tau = Integral(0 to v) v/(q^2 - v^2) ...